Reactive Forwarding and Proactive Forwarding Performance Comparison on SDN-Based Network - Suranegara, Galura Muhammad; Ichsan, Ichwan Nul; Setyowati, Endah (Department of Informatics, UIN Sunan Gunung Djati Bandung, 2020)
Software-defined networking (SDN) technology is one key technology in telecommunications networks that are currently widely studied. In SDN-based networks, the controller holds the key to the reliability of a network because all control functions are held by the controller as one of the open-source controllers, the Open Network Operating System (ONOS) has two forwarding mechanisms, namely reactive forwarding, and proactive forwarding. This study compares performance between reactive forwarding and proactive forwarding on ONOS with VM migration as traffic. The parameter measured is the total migration time using simple network topology. From the test results, the proactive forwarding scenario can optimize the fastest potential of the topology tested by using the path that has the largest bandwidth available on the network topology. In comparison, reactive forwarding can only pass through the smallest hops of the tested topology. From the measurement results, the average migration time performance using a proactive forwarding scenario is 36.16% faster than the reactive forwarding scenario.